مقترح لمقياس مكمم للمتغيرات المتعلقة بتقييم اداء التدريسي الجامعي من وجهة نظر التدريسيين - أ.د. شالل حبيب الجبوري (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The evaluation of teacher’s performance is very important subject .In order to do the evaluation and construct a scale of scores for the following anises which related to the teachers performance:  Axis of teaching  Axis of scientific research  Axis of community service We construct a questionnaire and distributed for sample of teachers in Lebanese French University and then analysis the respondent data by using some statistical tools, we get the following scale of evaluation:  Axis of teaching which got 35%.  Axis of scientific research which got 34%.  Axis of community service which got 31%. Although we suggest score for each main variable in each axis .Finally fixed some conclusions and recommendations.